Training in music - Anish, Blanche L., artist (Ohio : Federal Art Project, WPA in Ohio, 1937)
Poster announcing training opportunities in music in such areas as orchestra player, radio announcer, music salesman, concert singer, music teacher, radio singer, music critic, accompanist, and conductor, showing stylized piano, stringed instrument, and a hand conducting.